A modified ABS material and preparation method thereof

Through the combination of modified silica and aluminate coupling agent and microwave treatment, the stress cracking and uneven dispersion problems in modified ABS materials are solved, and its mechanical and conductive properties are significantly improved, and graphene and polymerization are achieved. The uniform dispersion and compatibility of the material system are improved.

CN118638383BActive Publication Date: 2025-01-07氢材科技(淮安)有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410723183.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-05
Publication Date
2025-01-07
Estimated Expiration
2044-06-05

AI Technical Summary

Technical Problem

The existing modified ABS materials are prone to stress cracking during use, and the uneven dispersion of graphene and polymer systems leads to a reduction in toughness performance. The compatibility of silica and organic polymer composites is poor, making it difficult to exert excellent performance. .

Method used

Modified silica is obtained by vapor deposition under an inert gas atmosphere, mixed with aluminate coupling agent and ground, adding TPU, ABS and mixed additives for melt mixing and microwave treatment to form graphene/dioxide Silicon nanocomposites improve their dispersion and compatibility in polymer systems.

Benefits of technology

The mechanical properties and conductive properties of the modified ABS materials are significantly improved, ensuring uniform dispersion of graphene and silica, enhancing the toughness and mechanical strength of the material, and improving the oxidation resistance and compatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004877818580000111
    Figure BDA0004877818580000111
Patent Text Reader

Abstract

The invention relates to a preparation method of a modified ABS material, and belongs to the technical field of modified ABS materials. The preparation method comprises the following steps: 1) preparing modified silicon dioxide; 2) preparing a modified mixture; 3) preparing a mixed material; 4) preparing a modified ABS material, wherein a silane coupling agent can perform surface modification on a polymer system and other components, thereby ensuring the contact effect between the modified mixture and other components in the polymer system, so that the modified mixture can be uniformly filled in the polymer system, and graphene and TPU can improve the toughness of the polymer system, thereby enhancing the bonding force between the polymer system and graphene and other components, thereby improving the mechanical properties of the modified ABS material. A stabilizer can improve the antioxidant properties of the modified ABS material, and the stabilizer can increase the stability of the components in the system, thereby preventing the modified ABS material from aging and decomposing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of modified ABS materials and relates to a modified ABS material and a preparation method thereof. Background Art

[0002] ABS is one of the world's most produced engineering plastics, but it will produce stress cracking during long-term use and transportation. As ABS is used in various fine components, more stringent requirements are placed on its performance. Cracking not only affects the appearance, but in severe cases it can also affect safety of use.

[0003] Nano-silicon dioxide has the appearance of amorphous white powder, with a particle size range of 1 to 100 nanometers, and a spherical microstructure with flocculent and mesh-like quasi-particle structures. Therefore, it has many unique properties, such as optical properties against ultraviolet rays, and can improve the anti-aging, strength and chemical resistance of other materials. However, there are a large number of hydroxyl groups on the surface of silicon dioxide nanoparticles, which are highly hydrophilic, resulting in poor compatibility with organic polymer composite materials, making it difficult to exert its excellent performance.

[0004] Graphene has good mechanical properties, thermal conductivity and electrical conductivity, and can be bent. Therefore, the graphene-enhanced polymer composite obtained by mixing graphene with a polymer system has good toughness and strength. However, due to the extremely large surface energy of graphene and the high scattering degree of phonons at the interface between graphene and the polymer system, the graphene in the graphene-enhanced polymer composite obtained by mixing graphene with the polymer system is unevenly dispersed, resulting in reduced toughness of the graphene-enhanced polymer composite.

[0005] A Chinese patent with publication number CN106084626A discloses a novel graphene flame-retardant ABS and a preparation method thereof, wherein the raw materials are graphene, ABS, polyethylene methyl acrylate, SBS, magnesium stearate, DCP, antimony trioxide, nano-silicon dioxide, pentaerythritol and TBAB; the patent document discloses that a modified ABS material is prepared by melt-plasticizing and granulating graphene, silicon dioxide and other materials, but the prepared modified ABS is prone to cracking due to uneven dispersion of graphene and silicon dioxide in the system. Summary of the invention

[0006] The object of the present invention is to provide a modified ABS material and a preparation method thereof, which has the characteristics of excellent mechanical properties.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A method for preparing a modified ABS material, the method comprising the following steps:

[0009] 1) placing silicon dioxide in a reactor, heating and controlling the pressure under an inert gas atmosphere, introducing a mixed gas for vapor deposition, and obtaining modified silicon dioxide;

[0010] 2) cooling the modified silica, adding an aluminate coupling agent, mixing and dispersing the mixture, and then grinding the mixture to obtain a modified mixture;

[0011] 3) adding TPU, ABS, mixed powder and mixing aid into the modified mixture, stirring and mixing evenly, and drying to obtain a mixed material;

[0012] 4) The mixed material is subjected to a first melt mixing, microwave treatment and a second melt mixing, and the material extruded after the melt mixing is dried and cooled to room temperature to obtain a modified ABS material.

[0013] As a preferred technical solution of the present invention, in step 1), the inert gas atmosphere is a nitrogen atmosphere; the heating condition is heating to 700-720°C at a heating rate of 30°C / min; and the speed of introducing the mixed gas is 0.15-0.25L / min.

[0014] As a preferred technical solution of the present invention, in step 1), the pressure control condition is to control the gas pressure in the reactor to 5.5-6.0 kPa; the mixed gas is a mixture of hydrogen and methane in a volume ratio of 1:8-10; the reactor is a microwave generator with a power of 2 kW; the amount ratio of silicon dioxide to the mixed gas is 1 g:5.0-7.0 L; in the scheme of the present invention, the microwaves generated by the microwave generator are transmitted to the reactor by a waveguide by using microwave plasma chemical vapor deposition (MPCVD), and a mixed gas of CH4 and H2 is introduced into the reactor. The high-intensity microwave energy excites methane to form active carbon-containing groups and atomic hydrogen, and forms plasma, thereby depositing a graphene film on the silicon dioxide.

[0015] As a preferred technical solution of the present invention, in step 2), the cooling condition is to cool to 85-90°C; the grinding condition is to grind for 2.0-2.5h under the grinding medium of 0.3mm zirconium oxide beads; the mass ratio of the modified silica to the aluminate coupling agent is 6-10:1; in the scheme of the present invention, the addition of the silica component has high mechanical strength and hardness, which can give the modified ABS material excellent mechanical properties, and its graphene has very high toughness. The combination of graphene and silica changes the compatibility of silica in the system, and the addition of graphene also improves the toughness of silica, so that the prepared silica / graphene nanocomposite material has the advantages of high conductivity and high mechanical strength.

[0016] Furthermore, the aluminate coupling agent used in the present invention is LD-B-1, which is purchased from Yangzhou Lida Resin Co., Ltd. The coupling agent uses a non-toxic, low-odor aluminate coupling agent. Since its inorganic-philic end and organic-philic end can chemically react with the surface of the inorganic filler and the ABS resin or form an entangled structure, the interface compatibility between the filler and the ABS resin is enhanced, the filler is evenly dispersed, the product quality is improved, and the production cost is reduced.

[0017] As a preferred technical solution of the present invention, in step 3), the mass ratio of the modified mixture, TPU, ABS, mixed powder and mixing additive is 6-8:8-10:40-50:2-3:7-9; the thermoplastic polyurethane elastomer TPU is a group copolymer elastomer composed of two microphase-separable phase segments, and contains a soft segment and a hard segment. It can form supramolecular forces with ABS through hydrogen bonds to toughen the ABS resin, thereby improving the processing fluidity of ABS and the bonding strength between material layers.

[0018] As a preferred technical solution of the present invention, in step 3), the mixing aid is formed by mixing white oil, PETS, stabilizer and silane coupling agent in a mass ratio of 1:1:0.8-1.0:0.5; the stabilizer is formed by mixing phosphite antioxidant 168 and hindered phenol antioxidant 1010 in a mass ratio of 1.5-2.0:1; the silane coupling agent is silane coupling agent KH-570; the mixed powder is formed by mixing zinc oxide and aluminum oxide in a mass ratio of 1:3; when the ordinary small molecule oxidant added to the TPU / ABS composite system accounts for about 2% of the total mass of the system material, the "microfibrillation" phenomenon is prone to occur This is because small molecule antioxidants have poor compatibility with the matrix polymer and are easily volatilized and migrated in the hot melt process, thus losing their antioxidant properties. The solution of the present invention can have very good compatibility with TPU / ABS materials by adding phosphite antioxidant 168 and hindered phenol antioxidant 1010 macromolecular antioxidants, which can be highly dispersed in the material, further enhancing the antioxidant effect, and at the same time delaying or inhibiting the aging process of the material, reducing the decomposition products of pentaerythritol stearate and the generation of oxides in the system, and solving the "microfibrillation" phenomenon by reducing the generation of tiny particles or fibers, thereby improving the mechanical properties of the modified ABS material.

[0019] As a preferred technical solution of the present invention, in step 3), the stirring and mixing conditions are stirring at 60-70°C; the drying conditions are drying at 100-105°C for 2.0-2.5h.

[0020] As a preferred technical solution of the present invention, in step 4), the first melt mixing and the second melt mixing are both completed in a twin-screw extruder; the conditions for the first melt mixing are mixing at 270-280° C. for 10-15 min; the conditions for the microwave treatment are microwave treatment at 500-800 W for 3-5 min; the conditions for the second melt mixing are mixing the microwave-treated masterbatch at 260-265° C. for 20-30 min; in the scheme of the present invention, the mixed material is melt-mixed for the first time so that the mixed material is mixed evenly after melting, the microwaves of the microwave treatment can penetrate into the interior of the material instead of relying on the heat conduction of the material itself, which can promote the mutual combination of the various material components and effectively improve the dispersibility of the various component materials in the system, and has the characteristics of high thermal energy utilization, energy saving, and pollution-free; the microwave-treated masterbatch is melt-mixed for the second time, and the masterbatch is further sheared and dispersed, so that graphene, silicon dioxide, mixed powder, etc. are evenly dispersed in the polymer system, thereby increasing its limit filling amount in the polymer system and ensuring that the modified ABS material has good mechanical properties.

[0021] As a preferred technical solution of the present invention, in step 4), the drying condition is at 100-105° C. and drying for 1-2 hours.

[0022] The invention discloses a modified ABS material prepared by the above-mentioned preparation method.

[0023] As a preferred technical solution of the present invention, the ABS is acrylonitrile-butadiene-styrene copolymer.

[0024] Beneficial effects of the present invention:

[0025] When preparing the modified ABS material of the present invention, the silane coupling agent can perform surface modification on the polymer system and other components, ensure the contact effect between the modified mixture and other components in the polymer system, so that the modified mixture can be uniformly filled in the polymer system, and the graphene and TPU can improve the toughness of the polymer system, so that the bonding force between the polymer system and the graphene and other components is enhanced, thereby improving the mechanical properties of the modified ABS material. The stabilizer can improve the antioxidant performance of the modified ABS material, and the stabilizer can increase the stability of the components in the system to prevent the modified ABS material from aging and decomposition. DETAILED DESCRIPTION

[0026] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0027] Example 1

[0028] A method for preparing a modified ABS material comprises the following steps:

[0029] 1) placing silicon dioxide in a reactor, heating and controlling the pressure under an inert gas atmosphere, introducing a mixed gas for vapor deposition, and obtaining modified silicon dioxide; wherein the inert gas atmosphere is a nitrogen atmosphere; the heating condition is heating to 700°C at a heating rate of 30°C / min; the speed of introducing the mixed gas is 0.15L / min; the pressure control condition is controlling the gas pressure in the reactor to 5.5kPa; the mixed gas is a mixture of hydrogen and methane in a volume ratio of 1:8; the reactor is a microwave generator with a power of 2kw; the amount ratio of silicon dioxide to the mixed gas is 1g:5.0L;

[0030] 2) cooling the modified silica, adding the aluminate coupling agent, mixing and dispersing, and then grinding to obtain a modified mixture; wherein the cooling condition is to cool to 85° C.; the grinding condition is to grind for 2.0 h under the grinding medium of 0.3 mm zirconium oxide beads; the mass ratio of the modified silica to the aluminate coupling agent is 6:1;

[0031] 3) Adding TPU, ABS, mixed powder and mixing aid to the modified mixture, stirring and mixing evenly, and drying to obtain a mixed material; wherein the mass ratio of the modified mixture, TPU, ABS, mixed powder and mixing aid is 6:8:40:2:7; the mixing aid is formed by mixing white oil, PETS, stabilizer and silane coupling agent in a mass ratio of 1:1:0.8:0.5; the stabilizer is formed by mixing phosphite antioxidant 168 and hindered phenol antioxidant 1010 in a mass ratio of 1.5:1; the silane coupling agent is silane coupling agent KH-570; the mixed powder is formed by mixing zinc oxide and aluminum oxide in a mass ratio of 1:3; the stirring and mixing evenly is performed at 60°C; the drying is performed at 100°C for 2.0h;

[0032] 4) subjecting the mixed material to a first melt mixing, microwave treatment and a second melt mixing, drying the melt mixed extruded material and cooling it to room temperature to obtain a modified ABS material; wherein the first melt mixing condition is at 270° C. and mixing for 10 min; the microwave treatment condition is at 500 W and microwave treatment for 3 min; the second melt mixing condition is mixing the microwave treated masterbatch at 260° C. for 20 min; the drying condition is at 100° C. and drying for 1 h.

[0033] Example 2

[0034] A method for preparing a modified ABS material comprises the following steps:

[0035] 1) placing silicon dioxide in a reactor, heating and controlling the pressure under an inert gas atmosphere, introducing a mixed gas for vapor deposition, and obtaining modified silicon dioxide; wherein the inert gas atmosphere is a nitrogen atmosphere; the heating condition is heating to 710°C at a heating rate of 30°C / min; the speed of introducing the mixed gas is 0.20L / min; the pressure control condition is controlling the gas pressure in the reactor to 5.8kPa; the mixed gas is a mixture of hydrogen and methane in a volume ratio of 1:9; the reactor is a microwave generator with a power of 2kw; the amount ratio of silicon dioxide to the mixed gas is 1g:6.0L; at this time, the content of graphene in the modified silicon dioxide is 65wt%.

[0036] 2) cooling the modified silica, adding the aluminate coupling agent, mixing and dispersing, and grinding to obtain a modified mixture; wherein the cooling condition is to cool to 88° C.; the grinding condition is to grind for 2.2 h under the grinding medium of 0.3 mm zirconium oxide beads; the mass ratio of the modified silica to the aluminate coupling agent is 8:1;

[0037] 3) Adding TPU, ABS, mixed powder and mixing aid to the modified mixture, stirring and mixing evenly, and drying to obtain a mixed material; wherein the mass ratio of the modified mixture, TPU, ABS, mixed powder and mixing aid is 7:9:45:2.5:8; the mixing aid is formed by mixing white oil, PETS, stabilizer and silane coupling agent in a mass ratio of 1:1:0.9:0.5; the stabilizer is formed by mixing phosphite antioxidant 168 and hindered phenol antioxidant 1010 in a mass ratio of 1.8:1; the silane coupling agent is silane coupling agent KH-570; the mixed powder is formed by mixing zinc oxide and aluminum oxide in a mass ratio of 1:3; the stirring and mixing evenly is performed at 65°C; the drying is performed at 102°C for 2.2h;

[0038] 4) subjecting the mixed material to a first melt mixing, microwave treatment and a second melt mixing, drying the melt mixed extruded material and cooling it to room temperature to obtain a modified ABS material; wherein the first melt mixing condition is at 275° C. and mixing for 12 min; the microwave treatment condition is at 650 W and microwave treatment for 4 min; the second melt mixing condition is mixing the microwave treated masterbatch at 262° C. for 25 min; the drying condition is at 102° C. and drying for 1.5 h.

[0039] Example 3

[0040] A method for preparing a modified ABS material comprises the following steps:

[0041] 1) placing silicon dioxide in a reactor, heating and controlling the pressure under an inert gas atmosphere, introducing a mixed gas for vapor deposition, and obtaining modified silicon dioxide; wherein the inert gas atmosphere is a nitrogen atmosphere; the heating condition is heating to 720°C at a heating rate of 30°C / min; the speed of introducing the mixed gas is 0.25L / min; the pressure control condition is controlling the gas pressure in the reactor to 6.0kPa; the mixed gas is a mixture of hydrogen and methane in a volume ratio of 1:10; the reactor is a microwave generator with a power of 2kw; the amount ratio of silicon dioxide to the mixed gas is 1g:7.0L;

[0042] 2) cooling the modified silica, adding the aluminate coupling agent, mixing and dispersing, and then grinding to obtain a modified mixture; wherein the cooling condition is to cool to 90° C.; the grinding condition is to grind for 2.5 hours under the grinding medium of 0.3 mm zirconium oxide beads; the mass ratio of the modified silica to the aluminate coupling agent is 10:1;

[0043] 3) Adding TPU, ABS, mixed powder and mixing aid to the modified mixture, stirring and mixing evenly, and drying to obtain a mixed material; wherein the mass ratio of the modified mixture, TPU, ABS, mixed powder and mixing aid is 8:10:50:3:9; the mixing aid is formed by mixing white oil, PETS, stabilizer and silane coupling agent in a mass ratio of 1:1:1.0:0.5; the stabilizer is formed by mixing phosphite antioxidant 168 and hindered phenol antioxidant 1010 in a mass ratio of 2.0:1; the silane coupling agent is silane coupling agent KH-570; the mixed powder is formed by mixing zinc oxide and aluminum oxide in a mass ratio of 1:3; the stirring and mixing evenly is carried out at 70°C; the drying condition is dried at 105°C for 2.5h;

[0044] 4) subjecting the mixed material to a first melt mixing, microwave treatment and a second melt mixing, drying the melt mixed extruded material and cooling it to room temperature to obtain a modified ABS material; wherein the first melt mixing condition is at 280° C. and mixing for 15 min; the microwave treatment condition is at 800 W and microwave treatment for 5 min; the second melt mixing condition is mixing the microwave treated masterbatch at 265° C. for 30 min; and the drying condition is at 105° C. and drying for 2 h.

[0045] Comparative Example 1

[0046] The modified ABS material includes the following preparation steps:

[0047] 1) After heating the mixture to 88° C., adding an aluminate coupling agent, mixing and dispersing, and then grinding to obtain a modified mixture; wherein the mixture is formed by mixing silica and graphene in a mass ratio of 7:13, and the grinding conditions are grinding for 2.2 hours under a grinding medium of 0.3 mm zirconium oxide beads; the mass ratio of the modified silica to the aluminate coupling agent is 8:1;

[0048] 2) Add TPU, ABS, mixed powder and mixing aid to the modified mixture, stir and mix evenly, and dry to obtain a mixed material; wherein the mass ratio of the modified mixture, TPU, ABS, mixed powder and mixing aid is 7:9:45:2.5:8; the mixing aid is formed by mixing white oil, PETS, stabilizer and silane coupling agent in a mass ratio of 1:1:0.9:0.5; the stabilizer is formed by mixing phosphite antioxidant 168 and hindered phenol antioxidant 1010 in a mass ratio of 1.8:1; the silane coupling agent is silane coupling agent KH-570; the mixed powder is formed by mixing zinc oxide and aluminum oxide in a mass ratio of 1:3; the stirring and mixing is carried out at 65°C; the drying is carried out at 102°C for 2.2h;

[0049] 3) subjecting the mixed material to a first melt mixing, microwave treatment and a second melt mixing, drying the melt mixed extruded material and cooling it to room temperature to obtain a modified ABS material; wherein the first melt mixing condition is at 275° C. and mixing for 12 min; the microwave treatment condition is at 650 W and microwave treatment for 4 min; the second melt mixing condition is mixing the microwave treated masterbatch at 262° C. for 25 min; the drying condition is at 102° C. and drying for 1.5 h.

[0050] Compared with Example 2, the difference is that, in Comparative Example 1, a mixture of silicon dioxide and graphene in a mass ratio of 7:13 is used instead of modified silicon dioxide.

[0051] Comparative Example 2

[0052] Step 2) cooling the modified silica, adding the aluminate coupling agent, mixing and dispersing, and stirring to obtain a modified mixture; wherein the cooling condition is cooling to 88° C.; the stirring time is 2.2 h; the mass ratio of the modified silica to the aluminate coupling agent is 8:1;

[0053] Compared with Example 2, the difference is that step 2) of Comparative Example 2 is not ground, and the other components, preparation steps and parameters are the same.

[0054] Comparative Example 3

[0055] Compared with Example 2, the difference is that no TPU is added in Comparative Example 3, and the other components, preparation steps and parameters are the same.

[0056] Comparative Example 4

[0057] Compared with Example 2, the difference is that no silane coupling agent is added in Comparative Example 4, and the other components, preparation steps and parameters are the same.

[0058] Comparative Example 5

[0059] Compared with Example 2, the difference is that the stabilizer in Comparative Example 5 is phosphate antioxidant 168, that is, hindered phenol antioxidant 1010 is not used, and the other components, preparation steps and parameters are the same.

[0060] Comparative Example 6

[0061] Compared with Example 2, the difference is that the stabilizer in Comparative Example 6 is hindered phenol antioxidant 1010, that is, phosphate antioxidant 168 is not used, and the other components, preparation steps and parameters are the same.

[0062] Comparative Example 7

[0063] Step 4) melt-mixing the mixed material, drying the melt-mixed extruded material, and cooling it to room temperature to obtain a modified ABS material; wherein the melt-mixing conditions are at 275° C. and mixing for 41 minutes; and the drying conditions are at 102° C. and drying for 1.5 hours.

[0064] Compared with Example 2, the difference lies in step 4), and the other components, preparation steps and parameters are the same.

[0065] Comparative Example 8

[0066] Step 4) The mixed material is melt-mixed for the first time and melt-mixed for the second time, and the melt-mixed extruded material is dried and cooled to room temperature to obtain a modified ABS material; wherein the first melt-mixing condition is at 275° C. and mixing for 16 minutes; the second melt-mixing condition is to mix the microwave-treated masterbatch at 262° C. for 25 minutes; and the drying condition is at 102° C. and drying for 1.5 hours.

[0067] Compared with Example 2, the difference lies in step 4), and the other components, preparation steps and parameters are the same.

[0068] The modified ABS materials obtained in Examples 1-3 and Comparative Examples 1-8 were tested for their performance, and the test results are shown in Table 1.

[0069] Table 1

[0070]

[0071] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-8, the mechanical properties of the modified ABS materials prepared in Examples 1-3 are significantly better than those of the modified ABS materials prepared in Comparative Examples 1-8.

[0072] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a modified ABS material, characterized in that: The preparation method comprises the following steps: 1) placing silicon dioxide in a reactor, heating and controlling the pressure under an inert gas atmosphere, introducing a mixed gas for vapor deposition, and obtaining modified silicon dioxide; the inert gas atmosphere is a nitrogen atmosphere; the heating condition is heating to 700-720°C at a heating rate of 30°C / min; the speed of introducing the mixed gas is 0.15-0.25L / min; the pressure control condition is controlling the gas pressure in the reactor to 5.5-6.0kPa; the mixed gas is a mixture of hydrogen and methane in a volume ratio of 1:8-10; the reactor is a microwave generator with a power of 2kw; the amount ratio of silicon dioxide to the mixed gas is 1g:5.0-7.0L; 2) cooling the modified silica, adding the aluminate coupling agent, mixing and dispersing, and then grinding to obtain a modified mixture; the mass ratio of the modified silica to the aluminate coupling agent is 6-10:1; 3) Add TPU, ABS, mixed powder and mixing aid to the modified mixture, stir and mix evenly, and dry to obtain a mixed material; the mass ratio of the modified mixture, TPU, ABS, mixed powder and mixing aid is 6-8:8-10:40-50:2-3:7-9; the mixing aid is prepared by mixing white oil, PETS, stabilizer and silane coupling agent in a mass ratio of 1:1:0.8-1.0:0.5; the mixed powder is prepared by mixing zinc oxide and aluminum oxide in a mass ratio of 1:3; the stabilizer is prepared by mixing phosphite antioxidant 168 and hindered phenol antioxidant 1010 in a mass ratio of 1.5-2.0:1; the silane coupling agent is silane coupling agent KH-570; 4) The mixed material is subjected to a first melt mixing, microwave treatment and a second melt mixing, and the material extruded after the second melt mixing is dried and cooled to room temperature to obtain a modified ABS material.

2. The method for preparing a modified ABS material according to claim 1, characterized in that: In step 2), the cooling condition is to cool to 85-90° C.; the grinding condition is to grind for 2.0-2.5 h with 0.3 mm zirconia beads as the grinding medium.

3. The method for preparing a modified ABS material according to claim 1, characterized in that: In step 3), the stirring and mixing conditions are stirring at 60-70° C.; the drying conditions are drying at 100-105° C. for 2.0-2.5 hours.

4. The method for preparing a modified ABS material according to claim 1, characterized in that: In step 4), the conditions for the first melt mixing are mixing at 270-280°C for 10-15 minutes; the conditions for the microwave treatment are microwave treatment at 500-800W for 3-5 minutes; the conditions for the second melt mixing are mixing the microwave treated masterbatch at 260-265°C for 20-30 minutes.

5. The method for preparing a modified ABS material according to claim 1, characterized in that: In step 4), the drying condition is at 100-105° C. for 1-2 hours.

6. A modified ABS material prepared by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Novel graphene flame-retardant ABS and preparation method thereof

    CN106084626A

  • High wear-resistant TPU material capable of being applied to 3D printing and preparation method thereof

    CN107641313A

  • Preparation method and product of silicon dioxide / graphene compound

    CN109850908A